From Christians to Europeans Pope Pius II and the concept of the modern Western identity - Bisaha, Nancy (Taylor & Francis, 2023)
Providing the first in-depth examination of Pope Pius II's development of the concept of Europe and what it meant to be 'European', From Christians to Europeans charts his life and work from his early years as a secretary in Northern Europe to his papacy.